(untitled) (Revista Brasileira Multidisciplinar, 2019)
The use of the transmission electron microscope (MET) is very widespread in the study of biological materials, since it allows the definition of intracellular images, allowing studies of cellular morphology and general aspects of organelles. The images are produced by the initial interaction of an electron beam with the sample, which is maintained under high vacuum conditions. Both the vacuum environment and the irradiation of the electrons during observation, represent adverse conditions for the sample, especially in the case of organic or biological materials, which are by nature hydrated, fragile and electrically insulating. Considering that there are several preparation techniques for MET, but few detailed description of these techniques in the literature, especially for the preparation of seedling roots, this work aimed to apply and adapt these techniques for the study of good quality of seedling roots. The samples were first washed in phosphate buffered saline solution, passed through the primary fixation with glutaraldehyde, then postfixed with osmium tetroxide, where they were subsequently dehydrated with acetone and infiltrated with Epon resin, finishing with polymerization, ultramicrotomy and sample staining. However, this detailed description of the methodology applied to seedlings root can be used safely and effectively by other people, since there are almost no adapted descriptions of MET methodology in the literature, especially for seedlings.